1982
DOI: 10.1002/bjs.1800690206
|View full text |Cite
|
Sign up to set email alerts
|

Tamponade and injection sclerotherapy in the management of bleeding oesophageal varices

Abstract: One hundred patients with bleeding oesophageal varices were randomized into two treatment groups after resuscitation. One group was managed by tamponade only (group 1); the other group (group 2) was treated by endoscopic injection of oesophageal varices. The patients in group 2 were further subdivided into 25 patients (group 2a), who had tamponade applied immediately after sclerotherapy, and 25 patients (group 2b), who had sclerotherapy without subsequent tamponade. Injection of varices controlled the acute bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(48 citation statements)
references
References 13 publications
1
47
0
Order By: Relevance
“…Conventional measures therapy, including blood and frozen plasma transfusion, fluid and including balloon tamponade, vasoconstrictors, and surgical electrolytes replacement, and lactulose, was administered to patients intervention did not substantially improve survival. [1][2][3] In the in both groups as clinically indicated. Oximeter monitoring was roupast 2 decades, endoscopic injection sclerotherapy (EIS) has tinely performed for both treatment groups during endoscopic therbeen widely employed in the management of bleeding from apy.…”
Section: Tion Was Associated With a Lower Complication Rate Thanmentioning
confidence: 99%
“…Conventional measures therapy, including blood and frozen plasma transfusion, fluid and including balloon tamponade, vasoconstrictors, and surgical electrolytes replacement, and lactulose, was administered to patients intervention did not substantially improve survival. [1][2][3] In the in both groups as clinically indicated. Oximeter monitoring was roupast 2 decades, endoscopic injection sclerotherapy (EIS) has tinely performed for both treatment groups during endoscopic therbeen widely employed in the management of bleeding from apy.…”
Section: Tion Was Associated With a Lower Complication Rate Thanmentioning
confidence: 99%
“…1 rate could be lowered [3][4][5][6][7][8] and survival prolonged. 4,6,9,10 Studies Patients who have bled from varices remain at risk with rubber band ligation have shown that in addition to for rebleeding.…”
mentioning
confidence: 99%
“…Randomized trials comparing tamponade to sclerotherapy for EVB show trends or significant benefit for sclerotherapy in initial hemostasis, and all indicate better sustained or definitive hemostasis with sclerotherapy. (6)(7)(8) Thus, tamponade for acute EVB is not better than medical therapy, is less effective than endoscopic therapy, and not uncommonly causes serious and sometimes fatal complications. My view has been that the use of tamponade should be exceedingly rare: e.g., patients with persistent massive known EVB awaiting endoscopy or awaiting transjugular intrahepatic portosystemic shunt after unsuccessful endoscopic intervention.…”
Section: Balloon Tamponadementioning
confidence: 99%